The United Kingdom transient ischaemic attack (UK-TIA) aspirin trial: final results. Issue 12 (December 1991) - Farrell, B; Godwin, J; Richards, S; Warlow, C
Abstract : From 1979-85, 2435 patients with a transient ischaemic attack or minor ischaemic stroke were randomly allocated to receive long term "blind" treatment with aspirin 600 mg twice daily (n = 815), aspirin 300 mg once daily (n = 806) or placebo (n = 814). No patient was lost to follow up. The "intention to treat" comparison included all the serious vascular events and deaths which occurred before the end of the follow up period on 30 September 1986. There was no difference in efficacy between the 300 mg and 1200 mg daily doses of aspirin, but the lower dose was undoubtedly less gastrotoxic. Also, there was no definite difference in the response of males and females to aspirin. The odds of suffering a major stroke, myocardial infarction or vascular death were 15% less in the combined aspirin groups compared with the placebo group (95% confidence interval 29% reduction to 3% increase in odds) which is compatible with the continuing overview of all the similar trials of antiplatelet drugs where the relative reduction in odds was 25%. There was no statistically significant reduction in the likelihood of either disabling major stroke and vascular death or vascular death occurring.